(untitled) (Damascus University Journal for the economic and Political sciences, 2024)
In times of crises and the collapse of the local currency exchange rate, and in light of the high rate of inflation, the country finds itself obligated to issue new money bills in circulation. The research is carried out to investigate this practice as its aim is to show the extent of the fluctuation of the exchange rate of the Syrian pound when issuing a new bill in circulation, especially that two bills were issued into circulation during the ongoing crisis in Syria which were 2000 and 5000 Syrian pounds. The research used the EVENT STUDY approach, considering that introducing a new money bill into circulation is an event that affects the exchange rate of the Syrian Pound against other foreign currencies. The research reached some results, and the most notable one is that there is an effect of issuing a new money bill on the average exchange rate, but the appropriate timing for this issuing should be chosen.